Study of histological and embryonic liver developments of rat fetuses before birth for days (10, 15, 19) (Tikrit Journal of Veterinary Science, 2024)
The liver is one of the vital organs in the body, playing a significant and essential role in performing a variety of functions that assist in supporting the immune system, digestion, metabolism, detoxification, and storage of vitamins, among other functions. Additionally, its active role extends throughout fetal life before birth. Therefore, the aim of this study was to investigate the developmental changes occurring in liver cells and tissues of fetuses before birth, specifically on days (10, 15, 19), and to understand its role and effective impact on fetal development. This study was conducted at the Animal House of the College of Veterinary Medicine at Tikrit University in Iraq. Laboratory rats obtained from the same study location were used, with a total of nine (9) rats, comprising six (6) females for tissue sectioning and three (3) males solely for mating purposes. The females were divided into three groups for days (10, 15, 19) before birth. After dissection and selection of the organs (liver parts), the samples were fixed, and tissue sections were prepared using hematoxylin and eosin staining. The results showed clear indications of the formation and development of various liver cells, including hepatocytes, bile ducts, and central veins, reflecting this development on fetal life. This developmental process persisted until birth.